Sustained attention deficit in bipolar disorder. - Clark, L; Iversen, S; Goodwin, G (2002)
BACKGROUND: Recovery in bipolar disorder is central to its definition but is rarely complete. Previous work has suggested that neuropsychological impairment persists during the euthymic state but has been confounded partly by mild affective symptoms in remitted patients. AIMS: To characterise neuropsychological functioning in the euthymic phase of bipolar disorder with an emphasis on tasks of executive functioning. METHOD: Thirty euthymic patients with bipolar disorder were compared with thirty healthy controls on neuropsychological tasks differentially sensitive to damage within prefrontal cortex. RESULTS: Bipolar I patients were impaired on tasks of attentional set shifting, verbal memory and sustained attention. Only sustained attention deficit survived controlling for mild affective symptoms. This deficit was related to progression of illness, but was none the less present in a subgroup of patients near illness onset. CONCLUSIONS: Sustained attention deficit may represent a neuropsychological vulnerability marker for bipolar disorder, providing a focus for further understanding of the phenotype and analysis of the neuronal networks involved.